United States Multicenter Clinical Trial of Corneal Collagen Crosslinking for Keratoconus Treatment - Hersh, Peter S; Stulting, R Doyle; Muller, David; Durrie, Daniel S; Rajpal, Rajesh K (Ophthalmology (Rochester, Minn.), 2017)
To evaluate the safety and efficacy of corneal collagen crosslinking (CXL) for the treatment of progressive keratoconus. Prospective, randomized, multicenter, controlled clinical trial. Patients with progressive keratoconus (n = 205). The treatment group underwent standard CXL and the sham control group received riboflavin alone without removal of the epithelium. The primary efficacy criterion was the change over 1 year of topography-derived maximum keratometry value, comparing treatment with control group. Secondary outcomes evaluated were corrected distance visual acuity (CDVA), uncorrected distance visual acuity (UDVA), manifest refraction spherical equivalent, endothelial cell count, and adverse events. In the CXL treatment group, the maximum keratometry value decreased by 1.6 diopters (D) from baseline to 1 year, whereas keratoconus continued to progress in the control group. In the treatment group, the maximum keratometry value decreased by 2.0 D or more in 28 eyes (31.4%) and increased by 2.0 D or more in 5 eyes (5.6%). The CDVA improved by an average of 5.7 logarithm of the minimum angle of resolution (logMAR) units. Twenty-three eyes (27.7%) gained and 5 eyes lost (6.0%) 10 logMAR or more. The UDVA improved 4.4 logMAR. Corneal haze was the most frequently reported CXL-related adverse finding. There were no significant changes in endothelial cell count 1 year after treatment. Corneal collagen crosslinking was effective in improving the maximum keratometry value, CDVA, and UCVA in eyes with progressive keratoconus 1 year after treatment, with an excellent safety profile. Corneal collagen crosslinking affords the keratoconic patient an important new option to decrease progression of this ectatic corneal process.